PENGARUH LATAR BELAKANG PENDIDIKAN TERHADAP PENGUASAAN KOMPETENSI PEDAGOGIK GURU SOSIOLOGI SMA SE KOTA PONTIANAK - Septiarti, Kiki; Rivaie, Wanto; Budjang, Gusti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Effect of Educational Background on Pedagogic Competence of  High School Sociology Teacher in Pontianak. The problem in this research was "How Educational Background Influence the Pedagogic Competence of Senior High School Sociology Teacher in Pontianak". This research was conducted descriptively using quantitative form. The technique which was used in this raasearch was observation and documentation with data collection using observation and interview form. The results showed: 1) The background of education gave influence on pedagogic competence of senior high school sociology teachers in Pontianak, 2) The results indicated that sociology teacher with background S1 Education differ with sociology teacher with background Non-Education, 3) There was a significant influence of educational background on competence pedagogic of sociology teachers in Pontianak. Thus, it can be concluded that, there was the influence of educational background on pedagogic competence of sociology teachers in Pontianak.                                                                                                                                                             1Q                                                                                                                                                                                                                                         Keywords: Educational Background, Pedagogic Competence